Melanization of Dirofilaria immitis Larvae in Different Culicid Species - Gílcia Aparecida de Carvalho; Rafael Antonio Nascimento Ramos; Rafael Trindade Maia; Carlos Fernando Salgueirosa de Andrade; Leucio Câmara Alves (Tehran University of Medical Sciences, 2018)
Background: Dirofilaria immitis is an important filarioid transmitted by culicids. The vector role of these arthropods may be influenced by biological events as melanization against D. immitis larvae. This study aimed to detect the occurrence of melanization in Culex quinquefasciatus, Aedes (Stegomyia) aegypti and Aedes (Stegomyia) albopictus experimentally infected with D. immitis. Methods: Five populations (Cx. quinquefasciatus RECIFE (P1), Ae. albopictus RECIFE (P2), Ae. aegypti RECIFE (P3), Ae. aegypti CAMPINAS (P4) and Ae. aegypti ROCKEFELLER (P5)) were artificially fed with infected blood containing D. immitis microfilariae. Ten mosquitoes per day from each population were dissected for 14 days. Results: Melanized larvae of D. immitis were observed in all population except in P3. The period in which melanized larvae were found varied from the third to the 14th day post-infection. Difference in the number of these larvae was observed between P5 and P2-P3 (P< 0.01), and between P5 and P4 (P< 0.05). Third-stage larvae of D. immitis were detected in all population 14 d post-infection, except in P3, which presented high mortality 24 h post-infection. The melanization observed in the populations herein studied did not indicate refractory since third-stage larvae were observed at the end of the experiment. Most likely, this immune response aimed to control the number of larvae, in order to maintain the equilibrium between vector-parasite. Conclusion: The melanization did not seem to be a limiting factor to the development of this filarioid in these local Brazilian Culicidae populations.